Relationship Between Students' Motivation and Reading Comprehension Achievement at the 4th Semester Students of English Language Education Study Program of STKIP Nias Selatan - Ndruru, Falentinus; Umiyati, Mirsa; Ndruru, Kalvintinus (KnE Social Sciences, 2022)
This research aimed to know the correlation between students’ motivation and reading comprehension achievement. This research was as kind of correlational research with Pearson Product Moment Formula. It was conducted at the 4